2012
DOI: 10.3174/ajnr.a3299
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Follow-Up Sonography and Clinical Improvement among Infants with Congenital Muscular Torticollis

Abstract: BACKGROUND AND PURPOSE:Infants grow rapidly, which causes the SCM to thicken physiologically. Therefore some cases of physiologically-thickened SCM can be confused with a poor response to physical therapy. There have been only a few quantitative ultrasonographic studies on the clinical outcome of rehabilitation for CMT. Our aim was to evaluate whether a new sonographic assessment method that uses the muscular thickness ratio of the SCM can help quantify the outcome of rehabilitation therapy for patients with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 11 publications
1
21
0
1
Order By: Relevance
“…Park et al [ 12 ] reported that the thickness of SCM in B-mode ultrasound was well correlated with PROM of neck. In clinical settings, however, physicians encountered several infants who showed similar thickness of SCM, but different PROM of neck, like group 1S and 1M in current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al [ 12 ] reported that the thickness of SCM in B-mode ultrasound was well correlated with PROM of neck. In clinical settings, however, physicians encountered several infants who showed similar thickness of SCM, but different PROM of neck, like group 1S and 1M in current study.…”
Section: Discussionmentioning
confidence: 99%
“…The classifications of the severity of SCM fibrosis using B-mode ultrasound have been reported. [ 9 , 11 ] B-mode ultrasound was well correlated with PROM of neck, [ 12 ] and feasible as it can be quickly implemented in a clinical setting. But it is inevitably subjective, semiquantitative (imprecise), and prone to inter-observer error.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital muscular torticollis (CMT) is a common congenital disorder in neonates and infants, showing incidence of 0.3% to 1.9% [ 28 - 30 ]. In previous studies, ultrasonographic findings showed focal or diffuse thickening in the lower two-thirds of the sternocleidomastoid muscle (SCM), with the size of the lesions ranging from 8 to 15.8 mm at the maximal transverse diameter and the length ranging from 13.7 to 45.8 mm [ 31 ].…”
Section: Torticollismentioning
confidence: 99%
“…However, there are some limitations in evaluating CMT using ultrasonography. First, the size of the SCM can decrease after physical therapy, which can affect its thickness and echogenicity [ 30 , 33 ]. In addition, the echogenicity and the maximum thickness of the SCM range widely, and for those demonstrating subtle changes, the diagnosis of CMT using ultrasonography can be challenging [ 31 - 34 ].…”
Section: Torticollismentioning
confidence: 99%
“…Ultrasound‐guided BoNT injections provide the most recent technique, which allows visualization of muscles, provides an atlas‐like observation, and also visualizes the diffusion of BoNT‐containing fluid out of the needle tip . Ultrasound‐guided injections are just beginning to be used in patients with CD or in pediatric patients . The combination of ultrasound and EMG is also possible, and dedicated probes are becoming available.…”
Section: Recent Developmentsmentioning
confidence: 99%